Determinan Partisipasi Petani dalam Skema Sertifikasi Kakao Rainforest Alliance di Kabupaten Poso - Meringgi, Amossius Rompolemba Andi Baso; Melumpi, Martho Harry; Kolompo, Septian Aditya (Syntax Corporation, 2025)
Low farmer participation in sustainable cocoa certification schemes poses a strategic challenge for enhancing the competitiveness of Indonesian cocoa products in global markets. This study aims to analyze the influence of social capital and gender roles on farmer participation in the Rainforest Alliance certification scheme in Poso Regency. Employing a cross-sectional design, the research involved 200 farm households (100 certified and 100 non-certified) selected through purposive sampling in South Pamona District. Data were analyzed using binary logistic regression to identify determinants of farmer participation. The analysis revealed a model prediction accuracy of 89.5% with a Nagelkerke R² of 0.856. Findings confirm that all dimensions of social capital have significant positive effects: farmer group membership (OR=8.899, p<0.001), participation intensity (OR=1.408, p<0.001), structural position (OR=2.259, p<0.01), social interaction (OR=1.307, p<0.05), and information access (OR=1.864, p<0.05). Regarding gender roles, women's involvement in production (OR=1.578, p<0.01), joint decision-making (OR=3.435, p<0.01), and joint income control (OR=2.440, p<0.05) showed significant effects, while household head gender was not significant (p=0.469). Significant farmer characteristics included education (OR=1.219, p<0.05), credit access (OR=2.573, p<0.05), and training participation (OR=6.399, p<0.001). This study confirms that the quality of social capital and gender dynamics in household decision-making are more determinant than demographic characteristics in explaining farmer participation in certification schemes. Policy implications include strengthening farmer group quality, adopting household-sensitive approaches in certification programs, facilitating financing access, and intensifying sustainable training programs.